Castillos de fracciones

Realiza las siguientes operaciones y simplifica el resultado.

10-\frac{\left( \frac{1}{4}+\frac{1}{6} \right)}{\left( \frac{1}{3}\right)^2}+3 \cdot \frac{5}{3}-7

SOLUCIÓN

Hacemos operaciones aparte
 \frac{1}{4}+\frac{1}{6} = \frac{3}{12}+\frac{2}{12} = \frac{5}{12}
\left( \frac{1}{3}\right)^2=\frac{1}{9}
\frac{5}{12} : \frac{1}{9} = \frac{45}{12} = \frac{15}{4}

Entonces tenemos:
10-\frac{\left( \frac{1}{4}+\frac{1}{6} \right)}{\left( \frac{1}{3}\right)^2}+3 \cdot \frac{5}{3}-7=
10-\frac{\frac{5}{12}}{ \frac{1}{9}}+3 \cdot \frac{5}{3}-7=
10-\frac{15}{ 4}+\cancel{3} \cdot \frac{5}{\cancel{3}}-7=
10-\frac{15}{ 4}+5-7=
8-\frac{15}{ 4}=
\frac{32}{4}-\frac{15}{ 4}=
\frac{17}{4}